1990
DOI: 10.1136/gut.31.9.989
|View full text |Cite
|
Sign up to set email alerts
|

Towards a true prevalence of peptic ulcer: the Sorreisa gastrointestinal disorder study.

Abstract: This study, designed to overcome methodological problems inherent in earlier prevalence studies of peptic ulcer, was carried out in a municipality in northern Norway. It included the total population of 2027, aged 20-69 years, and comprised a questionnaire and search for previously diagnosed peptic ulcers in the local medical records for all subjects, and additional endoscopy of all subjects with dyspepsia and their matched healthy controls (n=619). The overall prevalence was 10*5% in men and 9'5% in women, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
2

Year Published

1992
1992
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(66 citation statements)
references
References 12 publications
3
61
2
Order By: Relevance
“…On the basis of endoscopic findings, one Norwegian study reported an overall prevalence of 7.4% in men and 4.6% in women. 31 Similar frequency estimates for lifetime prevalence of verified ulcers were found in an unselected Danish population initially identified with self-reported ulcer (7.7% among men and 3.6% among women 32 ). Another large cross-sectional questionnaire-based survey conducted in northern Norway reported a 5.3% prevalence of peptic ulcer in men and 2.1% in women.…”
Section: Commentsupporting
confidence: 61%
“…On the basis of endoscopic findings, one Norwegian study reported an overall prevalence of 7.4% in men and 4.6% in women. 31 Similar frequency estimates for lifetime prevalence of verified ulcers were found in an unselected Danish population initially identified with self-reported ulcer (7.7% among men and 3.6% among women 32 ). Another large cross-sectional questionnaire-based survey conducted in northern Norway reported a 5.3% prevalence of peptic ulcer in men and 2.1% in women.…”
Section: Commentsupporting
confidence: 61%
“…These findings indicated that NSAID users with no symptoms did not undergo endoscopic examinations. Bernersen et al reported that only 1% of asymptomatic subjects had peptic ulcer disease (20). Although 25 of the 47 studied NSAID users had gastric or duodenal ulcers (53.2%), Laine and colleagues showed in a recent study that the incidence of peptic ulcer disease was 4.9 and 14.3% in aspirin and NSAID users, respectively (21).…”
Section: Discussionmentioning
confidence: 98%
“…It has been shown that the incidence of peptic ulcer disease has generally declined, and its prevalence has been estimated as 5-10% in the adult population in different countries (1). However, the number of patients affected by bleeding and perforation has not changed significantly (2) such that perforated ulceration affects up to 20% of peptic ulcer disease patients (3).…”
Section: Introductionmentioning
confidence: 99%